A coking efficiency improving pyrolysis furnace tube coating composition and a method for preparing the same
Patent Information
- Application Number
- CN202211080686.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-09-05
AI Technical Summary
Existing coatings for pyrolysis furnace tubes cannot effectively suppress coke formation under high-temperature conditions, resulting in long coking times and high energy consumption. Furthermore, the agglomeration of raw material components during coating preparation is uncontrollable, and the smoothness and wear resistance are insufficient.
A coating composition containing inorganic cellulose, organic binder, dispersant, aluminum powder, ammonium chloride, sodium fluoride, water-gas shift active component and alumina powder is used to form an aluminized coating on the surface of an alloy substrate through gas phase spraying and high-temperature solid phase aluminizing process, and the water-gas shift active component is introduced to catalyze coke gasification.
It significantly shortens the coking time of the pyrolysis furnace tube, improves coking efficiency, has a smooth coating surface and improved wear resistance, significantly increases coke conversion rate, and reduces fuel and steam waste.
Smart Images

Figure CN117684121B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ethylene cracking furnace tube protective coating technology, specifically relating to a cracking furnace tube coating composition for improving coking efficiency and its preparation method. Background Technology
[0002] Steam cracking, as the main technology for producing ethylene, mainly utilizes the thermal cracking reaction of hydrocarbon compounds to obtain ethylene products under high temperature conditions. This requires the steam cracking reactor material to have good high temperature resistance. Currently, the mainstream reactor material is often chromium-nickel alloy steel. However, the nickel and iron elements in this alloy will migrate under high temperature, accumulate on the inner surface of the steam cracking furnace tube, and accelerate the formation of coke as catalytic active centers. This greatly limits the operating efficiency of the steam cracking furnace.
[0003] Currently, most ethylene cracking furnace adjustments rely solely on past experience, making it impossible to determine the rationality of the furnace decoking cycle or accurately assess the decoking effect. Furthermore, the matching of coking steam and air in most ethylene plant cracking furnaces lacks rationality, leading to excessive coking steam volume, incomplete furnace tube decoking, or excessively long coking times (up to 72 hours), resulting in excessive fuel and steam waste, increased energy consumption, and decreased cracking furnace operating efficiency. To improve coking efficiency, shorten coking time, and reduce coking energy and material consumption, a common approach is to use solid powder embedding and co-infiltration technology. This involves preparing single-layer or multi-layer protective coatings on the surface of the alloy substrate. These coatings not only improve the alloy's oxidation and hot corrosion resistance but also act as a barrier, shielding the iron and nickel elements in the substrate and thus inhibiting coke formation during the reaction. Currently, infiltrating aluminum into the alloy substrate using solid powder embedding and co-infiltration technology to prepare an aluminized layer on the substrate surface is considered one of the most effective means to improve the alloy's oxidation resistance and mechanical properties and inhibit coking. Aluminizing technology has been widely used in the chemical industry.
[0004] Patent CN109055890A discloses a method for hot-diffusion preparation of a protective composite coating on ultra-high strength steel. The method uses co-diffusion technology to prepare a four-layer protective composite coating, consisting of an Fe-Zn and Fe-Al intermetallic compound diffusion layer, a Zn-rich layer, an aluminum-silicon alloy layer, and a micro / nano oxide layer from the inside out. Although this composite coating has high resistance to oxidation and nick corrosion, it also suffers from the following drawbacks: the raw material composition is relatively complex, and the thermal diffusion of each raw material component is different during the coating preparation process. This leads to uncontrollable agglomeration of the raw material components during co-diffusion, resulting in low coating smoothness, low wear resistance, and short service life.
[0005] Patent CN105695930A discloses a method for applying an aluminized silicon coating to the surface of boiler tubes with a large aspect ratio. This method involves spraying a pre-prepared aluminized silicon slurry onto a substrate, followed by drying, sintering, and sandblasting to prepare the aluminized silicon coating. While this coating technology can effectively suppress coking during the steam pyrolysis process when applied to pyrolysis furnace tubes, it cannot fundamentally prevent the formation and accumulation of coke on the coated tube surface. As the pyrolysis reaction continues, the coated tubes, like uncoated tubes, still require shutdown and the introduction of large amounts of high-temperature steam and air to burn off the accumulated coke. The burning time for these coated tubes is often the same as that for traditional pyrolysis furnace tubes.
[0006] Patent CN109868447A discloses a method for reducing the surface roughness of an aluminized layer. This method involves preparing a first aluminized layer on the surface of a substrate beforehand, and then preparing a second aluminized layer at a lower co-diffusion temperature after polishing the first aluminized layer. The surface roughness of the resulting double-layer aluminized layer is less than that of the aluminized layer prepared by existing aluminizing technology. Although this method can effectively reduce the surface roughness of the aluminized coating, the process is relatively complex, and the aggregation of aluminum atoms cannot be controlled during the co-diffusion process.
[0007] Patent CN104805399A discloses a colored slurry aluminizing process. The raw materials used in the preparation of the slurry include polyvinyl alcohol, sodium carboxymethyl cellulose, thickener, aluminum supply agent and water. Polyvinyl alcohol, sodium carboxymethyl cellulose or potassium carboxymethyl cellulose, thickener and water together constitute a binder. The function of the binder is to adhere the aluminum supply agent to the surface of the substrate, thereby making it easier for aluminum atoms to enter the interior of the substrate.
[0008] Patent CN113101935A discloses a method for preparing a nickel-based catalyst modified with metallic sodium: first, nickel-titanium hydrotalcite is synthesized using the urea method; then, the nickel-titanium hydrotalcite and a sodium salt solution are thoroughly mixed by wet impregnation, and the precipitate obtained after centrifugation is calcined and reduced in situ to prepare the nickel-based catalyst modified with metallic sodium. This catalyst has unique surface structure advantages and exhibits excellent catalytic performance for water-gas shift reactions. This preparation method is green, economical, simple, feasible, and energy-efficient, and the resulting supported catalyst has uniform composition, making it highly valuable for practical applications. However, the catalyst has a relatively low applicable temperature range of 300-450℃, making it unsuitable as an active component for coke burning in cracking furnace tubes. Summary of the Invention
[0009] To address the above technical problems, the present invention aims to provide a pyrolysis furnace tube coating composition for improving coking efficiency and its preparation method.
[0010] To achieve the above objectives, the present invention provides a coating composition for pyrolysis furnace tubes to improve coking efficiency, comprising the following components: 12-18 wt% inorganic cellulose, 1-5 wt% organic binder, 15-25 wt% dispersant, 20-25 wt% aluminum powder, 0.5-1.2 wt% ammonium chloride, 0.2-0.6 wt% sodium fluoride, 5-10 wt% water-gas shift active component, and 19-37 wt% alumina powder.
[0011] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention comprises 12-15 wt% inorganic cellulose, 1-3 wt% organic binder, 17-24 wt% dispersant, 21-25 wt% aluminum powder, 0.6-1.0 wt% ammonium chloride, 0.2-0.5 wt% sodium fluoride, 5-9 wt% water-gas shift active component, and 29-37 wt% alumina powder.
[0012] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention comprises inorganic cellulose, which is one or more of aluminum silicate fiber, asbestos fiber, quartz fiber, and mullite fiber, and the fiber length of the inorganic cellulose is 10-30 μm.
[0013] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention uses organic cellulose as the organic binder, preferably one or more of carboxymethyl cellulose, ethyl cellulose, and polyvinyl alcohol fiber.
[0014] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention includes a dispersant that is one or more of acetone, ethanol, tetrahydrofuran, and toluene.
[0015] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention comprises a water-gas shift active component that is a metal salt, preferably one or more of potassium carbonate, sodium carbonate, copper sulfate, ferrous sulfate, and ferric sulfate; the particle size of the water-gas shift active component is 50-70 nm.
[0016] The pyrolysis furnace tube coating composition for improving coking efficiency described in this invention comprises aluminum powder that is nano-sized with a particle size D90 of 50-100 nm; and alumina powder that is micron-sized with a particle size D90 of 2-10 μm.
[0017] To achieve the above objectives, the present invention also provides a method for preparing a coating for a pyrolysis furnace tube that improves coking efficiency, comprising the following steps:
[0018] S1, Prepare coating raw materials according to the composition described above;
[0019] S2, the prepared coating material is sprayed onto the surface of the substrate, and after drying, a coating is formed on the surface of the substrate;
[0020] S3 involves subjecting the coated substrate to high-temperature solid-phase aluminizing and water-gas transformation of active components under inert gas protection to obtain a coating that can improve coking efficiency.
[0021] The method for preparing the coating of the pyrolysis furnace tube for improving coking efficiency described in this invention involves spraying using a vapor phase spraying method in step S1, and the thickness of the coating after drying is 40-80 μm.
[0022] The method for preparing the coating of the pyrolysis furnace tube to improve coking efficiency according to the present invention uses argon as the inert gas. The high-temperature solid-phase aluminizing and water-gas transformation of active components are carried out in a high-temperature solid-phase aluminizing furnace at a temperature of 1000-1050°C for 8-10 hours.
[0023] Beneficial effects of this invention:
[0024] To further reduce the coking time of coated pyrolysis furnace tubes in existing technologies, this invention introduces a water-gas shift active component into the aluminizing coating. This active component utilizes the water-gas shift reaction mechanism to catalyze the gasification of intermediate products such as coke precursors during the pyrolysis reaction, thereby further inhibiting coking. Furthermore, this active component interacts with oxygen during the coking process of the coated furnace tube, achieving rapid gasification of coke. By reducing the coking time of the coated furnace tube, the restart time of the pyrolysis furnace can be significantly shortened, thereby improving the operating efficiency of the pyrolysis furnace.
[0025] In the coating preparation process, the present invention uses a binder to link inorganic fibers together. After drying, a fiber layer with a specific pore size is prepared on the surface of the substrate. This fiber layer can effectively inhibit the agglomeration of molten aluminum atoms and water-gas shift active components during the subsequent coating preparation process. As a result, the water-gas shift active components in the obtained aluminized coating are less likely to agglomerate with each other. At the same time, the highly dispersed active components can further improve the coke conversion efficiency during the coking process.
[0026] This invention is based on solid powder embedding co-infiltration technology, which infiltrates aluminum and active components that can catalyze coke-water-gas conversion into an alloy substrate to prepare an aluminized coating. This coating not only has a smooth surface, but can also catalyze coke gasification, greatly improving the coke burning rate of the pyrolysis furnace tube and achieving coke-free burning. Attached Figure Description
[0027] Figure 1 This is a scanning electron microscope image of the coating surface in Embodiment 1 of the present invention.
[0028] Figure 2 This is a scanning electron microscope image of the coating surface in Comparative Example 1 of the present invention. Detailed Implementation
[0029] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.
[0030] Using Cr25Ni35 as the substrate, several blank sample pieces of 30mm×15mm×5mm size were first processed. The sample pieces were sanded with sandpaper to remove the oxide layer on the surface of the sample pieces. Then, the sample surface was cleaned with acetone organic reagent to remove oil. After ultrasonic cleaning, the sample pieces were placed in a vacuum drying oven to dry for later use.
[0031] Comparative Example 1
[0032] 1. Degrease the surface of the blank sample piece;
[0033] 2. The coating is prepared according to the following weight percentages of raw materials: 25% aluminum powder, 0.8% ammonium chloride, 0.5% sodium fluoride, 51% alumina powder, and 22.7% acetone.
[0034] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 40μm.
[0035] 4. The substrate coated with the aluminizing agent is placed in an aluminizing chamber and subjected to high-temperature solid-phase aluminizing at 1040℃ for 9 hours under an argon protective atmosphere to obtain an aluminized coating. The surface morphology of the prepared coating is shown in the attached figure. Figure 1 As shown in the figure, the coating surface has many spherical protrusions, which are formed by the agglomeration of aluminum powder and alumina, resulting in uneven element distribution and high roughness on the coating surface.
[0036] Example 1
[0037] A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency includes the following steps:
[0038] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0039] 2. Prepare the coating according to the weight percentage of the raw materials, which are as follows: asbestos fiber 15%, organic binder ethyl cellulose 1%, acetone 25%, aluminum powder 21%, ammonium chloride 1.2%, sodium fluoride 0.4%, potassium carbonate 5%, and alumina powder 31.4%.
[0040] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 65μm.
[0041] 4. The coated substrate is placed in a diffusion chamber and subjected to high-temperature solid-phase aluminizing at 1040℃ for 9 hours under an argon protective atmosphere. This process yields a coating that improves coking efficiency. The surface morphology of the prepared coating is shown in the attached figure. Figure 2 As shown in the figure, the coating surface is smooth and has a porous structure, which increases the active sites of the water-gas conversion active components and helps to improve the coking rate of the coating surface.
[0042] Example 2
[0043] A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency includes the following steps:
[0044] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0045] 2. Prepare the coating according to the weight percentage of the raw materials, which are as follows: 18% aluminum silicate fiber, 5% carboxymethyl cellulose organic binder, 25% acetone, 22% aluminum powder, 1.0% ammonium chloride, 0.5% sodium fluoride, 6.5% sodium carbonate, and 22% alumina powder;
[0046] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 80μm.
[0047] 4. The coated substrate is placed in a diffusion chamber and kept at 1040℃ for 9 hours under an argon protective atmosphere to carry out high-temperature solid-phase aluminizing, and finally a coating that can improve coking efficiency is obtained.
[0048] Example 3
[0049] A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency includes the following steps:
[0050] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0051] 2. The coating is prepared according to the weight percentage of the raw materials, which are as follows: mullite fiber 12%, organic binder polyvinyl alcohol fiber 2.5%, toluene 23%, aluminum powder 25%, ammonium chloride 0.8%, sodium fluoride 0.2%, copper sulfate 7%, and alumina powder 29.5%.
[0052] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 72μm.
[0053] 4. The coated substrate is placed in a diffusion chamber and kept at 1040℃ for 9 hours under an argon protective atmosphere to carry out high-temperature solid-phase aluminizing, and finally a coating that can improve coking efficiency is obtained.
[0054] Example 4
[0055] A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency includes the following steps:
[0056] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0057] 2. Prepare the coating according to the weight percentage of the raw materials. The weight percentage of each raw material is as follows: 17.5% aluminum silicate fiber, 1.8% carboxymethyl cellulose organic binder, 15% tetrahydrofuran, 20% aluminum powder, 0.6% ammonium chloride, 0.6% sodium fluoride, 7.5% ferric sulfate, and 37% alumina powder.
[0058] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 64μm.
[0059] 4. Place the coated substrate in a diffusion chamber and perform high-temperature solid-phase aluminizing at 1050℃ for 10 hours under an argon protective atmosphere to finally obtain a coating that can improve coking efficiency.
[0060] Example 5
[0061] A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency includes the following steps:
[0062] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0063] 2. The coating is prepared according to the weight percentage of the raw materials, which are as follows: quartz fiber 14%, organic binder carboxymethyl cellulose 2%, ethanol 20%, aluminum powder 25%, ammonium chloride 0.6%, sodium fluoride 0.2%, ferrous sulfate 9%, and alumina powder 29.2%.
[0064] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 78μm.
[0065] 4. Place the coated substrate in a diffusion chamber and perform high-temperature solid-phase aluminizing at 1000℃ for 8 hours under an argon protective atmosphere to finally obtain a coating that can improve coking efficiency.
[0066] Comparative Example 2
[0067] Compared to Example 1, which did not include an organic binder, this coating preparation method includes the following steps:
[0068] 1. First, degrease the surface of the blank sample to remove oil stains from the substrate surface;
[0069] 2. Prepare the coating according to the weight percentage of the raw materials. The weight percentage of each raw material is as follows: asbestos fiber 16%, acetone 25%, aluminum powder 21%, ammonium chloride 1.2%, sodium fluoride 0.4%, potassium carbonate 5%, and alumina powder 31.4%.
[0070] 3. The prepared coating was sprayed onto the surface of the Cr35Ni45 alloy substrate using a vapor phase spraying method. After drying, the coating thickness was 55μm.
[0071] 4. Place the coated substrate in a diffusion chamber and perform high-temperature solid-phase aluminizing at 1040℃ for 9 hours under an argon protective atmosphere to obtain an aluminized coating.
[0072] Example 6
[0073] Coating scorching performance evaluation test
[0074] To further analyze and evaluate the coking performance of the aluminized coating, this invention employs a coking reaction evaluation device. The device has a reaction tube with a diameter of 3 cm and a length of 64 cm. Coated samples obtained in the above examples and comparative examples are suspended in the reaction tube. Naphtha and steam are introduced into the reaction tube for steam cracking reaction, causing coke to adhere to the surface of the coated samples. During the reaction, the mass flow rates of naphtha and steam are set to 0.45 mL / min and 0.60 mL / min, respectively, the reaction temperature is 810℃, and the reaction time is 8 h. After the reaction, the coated samples are removed and weighed, and the mass is recorded as M0. The reacted coated samples are then resuspended in the reaction tube, and steam and air are introduced into the reaction tube to coke the coated samples. During this process, the flow rates of steam and air are set to 0.6 mL / min and 80 mL / min, respectively, and the coking temperature is 840℃. The masses of the coated samples at coking times of 1 h, 3 h, 5 h, and 7 h are recorded as M. n The coke conversion rate X of the coated sample under different coking times was calculated using formula (1). n , where n is 1, 3, 5, or 7.
[0075] Xn%=(M0-M n ) / M0×100% (1)
[0076] Table 1
[0077]
[0078] As can be seen from Table 1, the aluminized coating containing water-gas shift active components prepared by the present invention has a better coke conversion rate under the same coking conditions. Taking a coking time of 1 hour as an example, the coke conversion rate of the aluminized coating of the present invention can reach 83.5%, while the coke conversion rate of the traditional aluminized coating is 45.1%.
[0079] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.
Claims
1. A coating composition for pyrolysis furnace tubes to improve coking efficiency, characterized in that, It includes the following components: 12-18 wt% inorganic cellulose, 1-5 wt% organic binder, 15-25 wt% dispersant, 20-25 wt% aluminum powder, 0.5-1.2 wt% ammonium chloride, 0.2-0.6 wt% sodium fluoride, 5-10 wt% water-gas shift active component, and 19-37 wt% alumina powder; The inorganic cellulose is one or more of the following: aluminum silicate fiber, asbestos fiber, quartz fiber, and mullite fiber; The organic binder is one or more of carboxymethyl cellulose, ethyl cellulose, and polyvinyl alcohol fiber; The dispersant is one or more of acetone, ethanol, tetrahydrofuran, and toluene; The active component of the water-gas conversion is one or more of potassium carbonate, sodium carbonate, copper sulfate, ferrous sulfate, and ferric sulfate.
2. The pyrolysis furnace tube coating composition for improving coking efficiency according to claim 1, characterized in that, The composition comprises 12-15 wt% inorganic cellulose, 1-3 wt% organic binder, 17-24 wt% dispersant, 21-25 wt% aluminum powder, 0.6-1.0 wt% ammonium chloride, 0.2-0.5 wt% sodium fluoride, 5-9 wt% water-gas shift active component, and 29-37 wt% alumina powder.
3. The pyrolysis furnace tube coating composition for improving coking efficiency according to claim 1, characterized in that, The length of the inorganic cellulose fibers is 10~30μm.
4. The pyrolysis furnace tube coating composition for improving coking efficiency according to claim 1, characterized in that, The particle size of the active component in the water-gas shift conversion is 50~70nm.
5. The pyrolysis furnace tube coating composition for improving coking efficiency according to claim 1, characterized in that, The aluminum powder is nano-sized, with a particle size D90 of 50~100nm; the alumina powder is micron-sized, with a particle size D90 of 2~10μm.
6. A method for preparing a coating for a pyrolysis furnace tube to improve coking efficiency, characterized in that, Includes the following steps: S1, prepare coating raw materials according to the composition of any one of claims 1 to 5; S2, the prepared coating material is sprayed onto the surface of the substrate, and after drying, a coating is formed on the surface of the substrate; S3 involves subjecting the coated substrate to high-temperature solid-phase aluminizing and water-gas shift reaction of active components under inert gas protection to obtain a coating that can improve coking efficiency.
7. The method for preparing the coating for improving coking efficiency of a pyrolysis furnace tube according to claim 6, characterized in that, In step S1, vapor phase spraying is used for spraying, and the thickness of the coating after drying is 40~80μm.
8. The method for preparing the coating for improving coking efficiency of a pyrolysis furnace tube according to claim 6, characterized in that, The inert gas is argon. The high-temperature solid-phase aluminizing and water-gas conversion of active components are carried out in a high-temperature solid-phase aluminizing furnace at a temperature of 1000~1050℃ for 8~10 hours.
